Body sway and movement strategies for control of postural stability in people with spinocerebellar ataxia type 3: A cross-sectional study. (July 2022) - Galvão, Ana Fernanda; Lemos, Thiago; Martins, Camilla Polonini; Horsczaruk, Carlos Henrique Ramos; Oliveira, Laura Alice Santos; Ferreira, Arthur de Sá
Abstract: Background: Postural instability with an excessive body sway is a disabling manifestation in spinocerebellar ataxia type 3. Whether the larger body sway reflects distinct movement strategies for postural control remains uncertain. This study compared the control of postural stability of people with spinocerebellar ataxia type 3 with healthy subjects using body sway and movement strategy analyses derived from bi- and three-dimensional posturography. Methods: Twenty-three patients (7 men, 16 women, 47 ± 11 years) and 102 healthy participants (34 men, 68 women; 44 ± 22 years) underwent posturography while standing with eyes open/closed tasks. Postural stability was assessed using elliptical area and average velocity of body sway. Spatial patterns (single-, double-, or multi-centered) were derived from the number of high-density regions in the three-dimensional statokinesigram. Findings: Repeated measures two-way analysis-of-variance showed a vision-by-group interaction effect for area ( F 1, 122  = 28.831, P  < 0.001, η 2  = 0.037) and velocity ( F 1, 123  = 59.367, P  < 0.001, η 2  = 0.073); sway area and velocity were higher in spinocerebellar ataxia type 3 and increased under eyes-closed condition, with a higher increase in the spinocerebellar ataxia type 3. A main effect for group ( F 1, 123  = 11.702, P  < 0.001, η 2  = 0.061) but not vision ( F 1, 123  = 2.257, P  = 0.136, η 2  = 0.005) was found for the number of high-density regions. Spatial patterns were different between groups under trials with eyes closed (χ 2 2, 125  = 7.46, P  = 0.023) but not open (χ 2 2, 125  = 2.026, P  = 0.363), with a shift from single- to double- or multi-centered spatial patterns. Interpretation: Compared to healthy subjects, a larger body displacement and velocity in spinocerebellar ataxia type 3, mainly under visual constraints, are not related to the predominance of either ankle or hip movement strategies. Highlights: Postural instability is a major disability in spinocerebellar ataxia type 3. Patients with spinocerebellar ataxia type 3 show large body sway. Single-centered spatial patterns are predominant in both patients and controls. A larger body sway is not related to the predominance of ankle or hip strategies.